Stages Of Implementation Of Distance Learning In Higher Education. - Khakimova Yoqutkhon Tokhirovna (Zien Journals, 2021)
The article provides information on the stages of the introduction of distance learning in higher education and the role of the teacher of higher education in the process of distance learning.
Keywords: Distance learning; online mode; satellite; e-learning